Evaluation of wireless information transmission channel settings of 802.11 wi-fi standard - Михалевський, Дмитро Валерійович (Eastern-European Journal of Enterprise Technologies, 2014)
Analysis of the basic settings of the wireless transmission channel for the 802.11 Wi-Fi standard networks was performed in the paper. For this purpose, channel structure that takes into account all kinds of interference that have a significant impact on the received signal power at the receiver input was proposed. In addition, based on the analysis of the transmission medium and channel settings, expression for assessing the signal power at the beginning of the receive path was obtained. It was found that one of the main characteristics that affect the wireless transmission channel throughput is the receiver sensitivity level. It defines a minimum allowable signal level at which the receiver can decode data with a set accuracy or set signal/noise ratio level. Another feature of the 802.11 standard is the fact that multi-level quadrature modulation is used to achieve high throughput. This type of modulation has high sensitivity to the transmission channel settings. Using high-order modulation primarily demands strict requirements for the receiver setting. Based on the transmission path research, it is possible to develop effective methods to assess and control characteristics of wireless 802.11 Wi-Fi standard networks, which should take into account the maximum possible number of influence factors.